2010
DOI: 10.1111/j.1471-4159.2009.06542.x
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective mechanism of 1‐(R)‐aminoindan, the major metabolite of the anti‐parkinsonian drug rasagiline

Abstract: J. Neurochem. (2010) 112, 1131–1137. Abstract The anti‐parkinsonian drug, rasagiline [N‐propargyl‐1‐(R)‐aminoindan; Azilect®], is a secondary cyclic benzylamine and indane derivative, which provides irreversible, potent monoamine oxidase‐B (MAO‐B) inhibition and possesses neuroprotective and neurorestorative activities. A prospective clinical trial has shown that rasagiline confers significant symptomatic improvement and demonstrated alterations in Parkinson’s disease progression. Rasagiline is primarily metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 67 publications
(149 reference statements)
0
29
0
1
Order By: Relevance
“…The major metabolites of N-dealkylation and/or hydroxylation are l-aminoindan, 3-hydroxy-N-propargyl-l-aminoindan and 3-hydroxy-l-aminoindan; biotransformation is virtually complete [5]. These metabolites do not inhibit MAO-B, but the major metabolite 1-aminoindan has neuroprotective properties that may contribute to the overall neuroprotective activity of rasagiline [12,23]. The major elimination pathway is urinary excretion of glucuronide conjugates of rasagiline and its metabolites.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…The major metabolites of N-dealkylation and/or hydroxylation are l-aminoindan, 3-hydroxy-N-propargyl-l-aminoindan and 3-hydroxy-l-aminoindan; biotransformation is virtually complete [5]. These metabolites do not inhibit MAO-B, but the major metabolite 1-aminoindan has neuroprotective properties that may contribute to the overall neuroprotective activity of rasagiline [12,23]. The major elimination pathway is urinary excretion of glucuronide conjugates of rasagiline and its metabolites.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…Monoamine oxidase type-B (MAO-B) inhibitors have returned to the spotlight as an alternative to dopaminergic replacement therapy and studies have demonstrated that they enhance cognitive function (2) and exert neuroprotective effects (3). Disease modification has also been investigated in previous studies, assessing the effects of the MAO-B inhibitors, selegiline and rasagiline (3,4). Although selegiline, the first selective inhibitor of MAO-B, has been widely used in patients with PD as monotherapy and adjuvant therapy, its basic and clinical pharmacological effects have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Rasagiline is a newer propargylamine derivative and more potent MAO-B inhibitor than selegiline. Some reports also suggest that the aminoindan metabolite of rasagiline confer additional neuroprotective activity [9]. Rasagiline has been studied using a delayed-start clinical trial design intended to reduce the confounding effect of symptomatic efficacy.…”
Section: Antioxidantsmentioning
confidence: 99%